Molecular Identification and Traceability of Illegal Trading in Lignobrycon myersi (Teleostei: Characiformes), a Threatened Brazilian Fish Species, Using DNA Barcode - Alexandre dos Santos Rodrigues; José Henrique Souza Galdino Brandão; Jamille de Araújo Bitencourt; Ricardo Jucá-Chagas; Iracilda Sampaio; Horácio Schneider; Paulo Roberto Antunes de Mello Affonso (The Scientific World Journal)
Lignobrycon myersi is a threatened freshwater fish species and endemic of a few coastal rivers in northeastern Brazil. Even though the Brazilian laws prohibit the fisheries of threatened species, L. myersi is occasionally found in street markets, being highly appreciated by local population. In order to provide a reliable DNA barcode dataset for L. myersi, we compared mitochondrial sequences of cytochrome c oxidase subunit I (COI) from fresh, frozen, and salt-preserved specimens. Phylogenetically related species (Triportheus spp.) and other fish species (Astyanax fasciatus) commonly mixed with L. myersi in street markets were also included to test the efficiency of molecular identification. In spite of the differences in conservation processes and advanced deterioration of some commercial samples, high-quality COI sequences were obtained and effective in discriminating L. myersi specimens. In addition, while populations from Contas and Almada River basins seem to comprise a single evolutionary lineage, the specimens from Cachoeira River were genetically differentiated, indicating population structuring. Therefore, DNA barcoding has proved to be useful to trace the illegal trading of L. myersi and to manage threatened populations, which should focus on conservation of distinct genetic stocks and mitigation on human impacts along their range.